Early Childhood Caries and the Impact of Current U.S. Medicaid Program: An Overview - Bussma Ahmed Bugis (Hindawi Limited, 2012)
Pediatric dental caries is the most common chronic disease among children. Above 40% of the U.S. children aged 2-11 years have dental caries; more than 50% of them come from low-income families. Under dental services of the Medicaid program, children enrolled in Medicaid must receive preventive dental services. However, only 1/5 of them utilize preventive dental services. The purpose of this overview is to measure the impact of Medicaid dental benefits on reducing oral health disparities among Medicaid-eligible children. This paper explains the importance of preventive dental care, children at high risk of dental caries, Medicaid dental benefits, utilization of dental preventive services by Medicaid-eligible children, dental utilization influencing factors, and outcome evaluation of Medicaid in preventing dental caries among children. In conclusion, despite the recent increase of children enrolled in Medicaid, utilizing preventive dental care is still a real challenge that faces Medicaid.